NOTE ON THE PRAWN FISHERY IN THE GULF OF KUTCH DURING 1962-63 - Deshmukh, V M (Indian Journal of Fisheries, 2011)
The monsoon fishery of August-September in the creeks, and the winter fishery of October-November in the gulf form the two main prawn-fishing seasons in the Gulf of Kutch. The monsoon fishery is supported by Metapenaeus kutchensis, while the winter fishery, by M. kutchensis, M. hrevicornis and Penaeus indicus. The pattern of distribution of these species indicates that there is a higher abundfuice of M. kutchensis in the Inner gulf and P. indicus and M. brevkornis in the outer gulf. The average growth rate of juveniles of M. kutchensis is found to be 6.7 mm per month. Sex-ratio distribution shows preponderance of females in the catches. The fluctuation in the landings of the monsoon months shows correlation with the salinity of the creek; relatively better landings occur coinciding with the lowering of salinity.